2015
DOI: 10.4174/astr.2015.89.3.117
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastric tube formation with pyloromyotomy for reconstruction in patients with esophageal cancer

Abstract: PurposeTo analyze the benefit and feasibility of this procedure compared with those of open method.MethodsAbdominal procedure includes laparoscopic gastric mobilization, celiac axis lymph node dissection, formation of the gastric tube, and pyloromyotomy. The actual procedure performed during open surgery is the same as those of laparoscopic surgery except for the main incision. Minimally invasive esophagectomy (MIE) was performed on 54 patients with esophageal cancer. The short-term outcomes, including postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…al 16. demonstrated that the only difference between MIE and open surgery is the abdominal operative time (90 ± 27.6 minutes in the laparoscopic group vs 162 ± 97.3 minutes in the open group; p < 0.001), which is consistent with our finding (76 ± 15 minutes vs 125 ± 25 minutes, respectively, in laparoscopic and open group; p < 0.05).…”
supporting
confidence: 92%
“…al 16. demonstrated that the only difference between MIE and open surgery is the abdominal operative time (90 ± 27.6 minutes in the laparoscopic group vs 162 ± 97.3 minutes in the open group; p < 0.001), which is consistent with our finding (76 ± 15 minutes vs 125 ± 25 minutes, respectively, in laparoscopic and open group; p < 0.05).…”
supporting
confidence: 92%
“…The review identified 98 studies 6,7,34–129 comparing surgical approaches for oesophagectomy, involving 32 315 patients ( Fig . 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Partial gastric tubing procedure were performed using linear stapler at distal two third of stomach alongside lesser curvature with creation of 5 to 6 cm width of the stomach. Regional lymph nodes were dissected during the procedure without jejunostomy [ 4 , 5 ].…”
Section: Methodsmentioning
confidence: 99%